Attitudes of Consumers Towards Islamic and Conventional Credit Cards in Indonesia - Sylva Alif Rusmita; Shochrul Rohmatul Ajija (Faculty of Economic and Business, 2017)
This study aims to analyze the attitudes of consumers towards Islamic and conventional credit cards. Using online questionnaire survey data from 51 respondents in Surabaya, East Java, the study revealed that most consumers possessed credit cards because of their convenience factor, relationship with their existing bank, and card salesmen. Therefore, the sale is the most powerful way to invite the community to have an Islamic credit card. Many customers do not care whether their credit cards are Islamic based or not, as long as the salesman promoted cards to them and the cards are able to meet their personal needs, especially for sales and purchase transactions online, they will utilize the cards. The large number of Muslims in Surabaya should be a share of the lucrative market for Islamic credit cards. Therefore, the education about the Islamic manner of consumption and the dangers of usury should be promoted in Surabaya.DOI: 10.15408/etk.v16i2.5519